Machinability analysis of Albromet W130 copper alloy by WEDM - Mouralová, Kateřina; Bednář, Josef; Beneš, Libor; Zahradníček, Radim; Fries, Jiří (Springer, 2024)
The unconventional Wire Electrical Discharge Machining (WEDM) technology represents a vital manufacturing technology in different industrial branches, such as aviation, military, automotive or energy industry. The WEDM energy demand is considerable and it is, therefore, desirable to reduce the machining time by optimising the machining parameters. In the study, the chosen parameters were Pulse off time, Gap voltage, Discharge current, Pulse on time, and Wire feed. Another factor we investigated in our Box-Behnken design of experiment was the workpiece thickness. The cutting speed, topography, and surface morphology were analysed in the samples produced for the design of experiment. This investigation was carried out using electron microscopy. The chemical composition of individual spots was analysed as well. The samples were found not to have significant differences in the appearance of craters on the edge and in the centre. Similarly, there was no significant difference observed between thicknesses and different parameter settings. The surfaces also show a large number of small bubbles. There were, however, no cracks or other defects found, even in the cross-sections of all samples.

The unconventional Wire Electrical Discharge Machining (WEDM) technology represents a vital manufacturing technology in different industrial branches, such as aviation, military, automotive or energy industry. The WEDM energy demand is considerable and it is, therefore, desirable to reduce the machining time by optimising the machining parameters. In the study, the chosen parameters were Pulse off time, Gap voltage, Discharge current, Pulse on time, and Wire feed. Another factor we investigated in our Box-Behnken design of experiment was the workpiece thickness. The cutting speed, topography, and surface morphology were analysed in the samples produced for the design of experiment. This investigation was carried out using electron microscopy. The chemical composition of individual spots was analysed as well. The samples were found not to have significant differences in the appearance of craters on the edge and in the centre. Similarly, there was no significant difference observed between thicknesses and different parameter settings. The surfaces also show a large number of small bubbles. There were, however, no cracks or other defects found, even in the cross-sections of all samples.
Machinability analysis of Albromet W130 copper alloy by WEDM
Keywords: WEDM; wire electrical discharge machining; Albromet W130; design of experiment; machining parameters; WEDM; wire electrical discharge machining; Albromet W130; design of experiment; machining parameters